Analysis of cash waqf development in Indonesia using Interpretive Structural Modeling (ISM) - Rusydiana, Aam Slamet (Journal of Islamic Economics Lariba, 2018)
This study aims to identify the main factors that were obstacles to develop the implementation of cash waqf in Indonesia using Interpretive Structural Modeling (ISM) method. ISM is an advanced design methodology used to identify, to analyze, and to summarize different relationship among factors that elucidate a problem, model or issue. The development of cash waqf in Indonesia with ISM framework is divided into three criteria: (1) Challenges (aspects) faced in developing cash waqf, (2) Strategy or foundation required within the framework of developing cash waqf, and (3) Stakeholders or actors involved in the development of the cash waqf. The result shows that the core problems and challenges faced in the development of cash waqf institution are: System aspect, product, regulation and information technology. The core strategies or foundations that are needed in a framework of cash waqf development are Transparency and accountability of waqf institutions, Quality development of nadzir, and Innovative marketing strategy from waqf institution.